VALIDITY OF PROBLEM-BASED SCIENCE PRACTICAL INSTRUCTIONS - Irwandi Rahmat (Journal Analytica Islamica, 2024)
This research aims to test the level of validity of problem- based science practicum instructions aimed at class VIII SMP/MTs students in odd semesters. The problem-based approach was chosen because it was proven to be effective in improving students' critical thinking and problem solving skills. This research uses part of the 4D method which consists of definition, design and development. The results of this research show that the problem-based practicum instructions developed are valid, with a validity value of 4.2, which means that the problem-based practicum instructions are included in the valid criteria. It is hoped that the final product resulting from this research can be a reference for teachers in teaching science using a problem-based approach, so that it can improve the quality of science learning in schools.